1989
DOI: 10.1128/mcb.9.8.3473
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the TRPM-2 gene in cells undergoing programmed death.

Abstract: RNA and protein products encoded by the testosterone-repressed prostate message-2 gene (TRPM-2) are induced to high levels, coordinate with the onset of cell death, in numerous rodent models of inducible tissue damage. These models include cell death initiated by hormonal stimuli (prostate regression), pressure insult (renal atrophy after ureteral obstruction), developmental stimuli (necrosis of interdigital tissue), and cytotoxic injury (chemotherapeutic regression of a tumor). Sequence analysis of cDNA encod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
200
3
1

Year Published

1995
1995
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 449 publications
(212 citation statements)
references
References 43 publications
6
200
3
1
Order By: Relevance
“…This induction is more rapid than that of mdm-2, in agreement with the pro- Table 1 Expression of genes indentified by their diffential expression during apoptosis Gene(s) Induced in Expression in REtsAF Calmodulin, chondroitin sulfate Glucocorticoids induced thymocyte apoptosis [11,20] Not detected proteoglycan core protein RP8 Glutathione S-transferase Ybl Clusterin Ubiquitin Glucocorticoids or radiation induced thymocyte apoptosis [15] Prostate regression [32] and steroid induced lymphocyte apoptosis [21] Prostate regression and various other cell death process [17] Radiation-induced lymphocyte apoptosis [18] and insect muscles degeneration [19] [29], which suggest that, in some cells, p53 can mediate apoptosis by repressing survival genes. Recently, a reevaluation of the role of de novo protein synthesis in thymocyte apoptosis has also suggested that inhibitors of protein synthesis may delay apoptosis rather than prevent it [30], suggesting that some of the components of the apoptotic machinery are already present before apoptosis induction.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…This induction is more rapid than that of mdm-2, in agreement with the pro- Table 1 Expression of genes indentified by their diffential expression during apoptosis Gene(s) Induced in Expression in REtsAF Calmodulin, chondroitin sulfate Glucocorticoids induced thymocyte apoptosis [11,20] Not detected proteoglycan core protein RP8 Glutathione S-transferase Ybl Clusterin Ubiquitin Glucocorticoids or radiation induced thymocyte apoptosis [15] Prostate regression [32] and steroid induced lymphocyte apoptosis [21] Prostate regression and various other cell death process [17] Radiation-induced lymphocyte apoptosis [18] and insect muscles degeneration [19] [29], which suggest that, in some cells, p53 can mediate apoptosis by repressing survival genes. Recently, a reevaluation of the role of de novo protein synthesis in thymocyte apoptosis has also suggested that inhibitors of protein synthesis may delay apoptosis rather than prevent it [30], suggesting that some of the components of the apoptotic machinery are already present before apoptosis induction.…”
Section: Discussionsupporting
confidence: 62%
“…Clusterin, also called TRPM-2 and SGP-2, is an early indicator of programmed cell death [17]. The product of this gene is a sulfated glycoprotein the function of which remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptotic cell death is accompanied by condensation and fragmentation of nuclei, loss of plasma membrane microvilli, condensation of cytoplasm, and fragmentation of chromosomal DNA into 180 bp oligomers and encountered in post embryonic and embryonic development (Wyllie et al, 1980;Buttyan et al, 1989). Apoptosis also plays the dominant role in various physiological cell death and disease states (Nagata and Golstein 1995;Suzuki et al, 1996a ± c;Nagata, 1997).…”
Section: Introductionmentioning
confidence: 99%